2020
DOI: 10.1016/s1473-3099(20)30154-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mutations associated with resistance to macrolides and fluoroquinolones in Mycoplasma genitalium: a systematic review and meta-analysis

Abstract: Background: We summarised data from studies reporting on macrolide and fluoroquinolone resistanceassociated mutations in Mycoplasma genitalium, examined temporal trends, and associations with geographical location, sex and population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
197
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(230 citation statements)
references
References 81 publications
14
197
2
9
Order By: Relevance
“…The mutations in 23S rRNA and parC have been identi ed as the cause of failure of macrolide and quinolone in the treatment of M. genitalium [53,54]. In our study, 66.4% (101/152) and 77.7% (108/139) of samples manifested mutations in 23S rRNA and parC genes, and A2072G (59/101, 58.4%) and S83I (79/108, 73.1%) were highly predominating in 23S rRNA and parC genes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The mutations in 23S rRNA and parC have been identi ed as the cause of failure of macrolide and quinolone in the treatment of M. genitalium [53,54]. In our study, 66.4% (101/152) and 77.7% (108/139) of samples manifested mutations in 23S rRNA and parC genes, and A2072G (59/101, 58.4%) and S83I (79/108, 73.1%) were highly predominating in 23S rRNA and parC genes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The univariable analysis showed that women who were younger, in their first pregnancy, employed, single or separated, had never used a modern method of contraception, or had abnormal vaginal discharge at any time in their current pregnancy were at increased risk for certain STIs, to varying degrees of statistical significance. In the multivariable analysis, primigravida women and those 16 16; p = 0.02).…”
Section: Factors Associated With Curable Stismentioning
confidence: 93%
“…In pregnant women, estimates range from 0.7% in the United Kingdom (14) to 11.9% in the Solomon Islands (15). During 2010-2019, global macrolide resistance to M. genitalium increased from 10% to >50% (16). In many regions, the prevalence of M. genitalium and its susceptibility to antimicrobial drugs is unknown.…”
mentioning
confidence: 99%
“…The macrolide azithromycin is the currently recommended first-line treatment, but macrolide resistance mutations (MRMs) arising from single nucleotide changes to the 23S rRNA gene confer resistance to treatment. These mutations are becoming increasingly common, with a recent meta-analysis finding an increase in prevalence from 10.0% [95% confidence interval (CI) 2.6-20.1%] prior to 2010, to 51.4% (40.3-62.4%) in 2016-17 [3]. The prevalence of resistance in some specific populations is even higher, with MRM levels of 84.2% reported in asymptomatic men who have sex with men in Australia [4].…”
Section: Introductionmentioning
confidence: 99%
“…The second-line therapy in many guidelines is the fluoroquinolone moxifloxacin, to which resistance is also increasing [3]. In the context of high levels of resistance, the use of diagnostic tests that also detect resistance mutations has shown promise for directing clinicians towards prescribing the most efficacious treatment (known as 'resistance-guided therapy'), with corresponding increases in overall levels of cure [5,6].…”
Section: Introductionmentioning
confidence: 99%